#### Answer

$5^x(\frac{5^h-1}{h})$

#### Work Step by Step

$\frac{f(x+h)-f(x)}{h}=\frac{5^{x+h}-5^x}{h}=\frac{5^x\cdot5^h-5^x}{h}=5^x(\frac{5^h-1}{h})$

Published by
Cengage Learning

ISBN 10:
1285741552

ISBN 13:
978-1-28574-155-0

$5^x(\frac{5^h-1}{h})$

$\frac{f(x+h)-f(x)}{h}=\frac{5^{x+h}-5^x}{h}=\frac{5^x\cdot5^h-5^x}{h}=5^x(\frac{5^h-1}{h})$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.